Chinese Extractive Industry in Peru: Shougang Hierro Peru, 1993-2013 - Zapata, María de los Ángeles (2017)
ftis research project documents the China incoming to the Peruvian industry, focusing on mining. fte investment measures should be made not only in monetary terms but also taking into account their contribution to local development, considering minerals are non-renewable resources. At the core of the thesis, the Shougang Hierro Peru (SHP) case is discussed. ftere are three main dimensions addressed: social, environmental and economic, based on the sustainable development concept, in order to assess the mining investment quality and its relations with its main stakeholders: local government (municipality), workers unions (employees), and civil society (Marcona inhabitants).fte main hypothesis is that the SHP behavior, given its Chinese source, represents a successful model of FDI extractive industry, distinct from the political democracy. SHP is found as a unique and emblematic case, due to its access conditions to Peru, in the context of a government that followed the Washington Consensus policies and allowed a Law-Contract that, until 2016, provided them free use and domain of basic services, water and electricity. SHP is a special case and there are no related mining project with similar characteristics; nevertheless, in order to have control cases, we made a brief comparison using greenfield and brownfield projects, Antamina (Huari, Ancash) and Doe Run (La Oroya, Junín), respectively.ftis investigation, and many authors as well, agree on a same general conclusion: the quality of mining investments projects depends on the national regulatory framework. Without a Government that actively monitors the mining companies’ behavior and establishes fair conditions for population as well as private sector, they would probably prefer the minimum quality standards.